Características del consumo de filgrastim 300mcg/ml en pacientes hospitalizados en el servicio de onco-hematología de adultos del hospital Víctor Lazarte Echegaray en el año 2013 - Zapata Chávez, Patricia Elizabeth (2014)
This study aims to determine the characteristics of consumption Filgrastim 300mcg/ml prescribed inpatient service in Onco-Hematology adults Victor Lazarte Echegaray Hospital in 2013, for which a descriptive cross-sectional study was conducted retrospective drug utilization. We worked with computerized report consumption Filgrastim in patients hospitalized in the service of Onco-Hematology adults Victor Lazarte Echegaray Hospital records. It is concluded that in the study of the total Service Filgrastim consuming 54% are female and 46% were male; the diagnosis of major consumption of this drug is in lymphoblastic leukemia with 32.14%, the average annual consumption expressed in Defined Daily Doses (DDD) per 100 beds - day was 12.34%. The change is not statistically significant during the study period. The cost of the annual consumption of Filgrastim 300mcg/ml was S /. 12688.13 soles